2014
DOI: 10.1007/s11060-014-1395-4
|View full text |Cite
|
Sign up to set email alerts
|

MGMT promoter methylation in plasma of glioma patients receiving temozolomide

Abstract: 1Promoter methylation of the O6-methylguanine-DNA methyltransferase (MGMT) gene plays 2 a role in cellular response to alkylating agents. In the present study aimed to: i) evaluate the 3 concordance between MGMT promoter methylation status in tumor tissue and plasma; ii) 4 monitor MGMT promoter methylation status in plasma taken before and during 5 temozolomide treatment; iii) explore the value of MGMT promoter methylation status in 6 plasma as a prognostic/predictive biomarker in glioma patients. 7We enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 37 publications
0
27
0
1
Order By: Relevance
“…More recently, a meta-analysis of 10 eligible studies, including the MGMT methylation status of more than four thousand subjects, confirmed that patients bearing this genotype present longer overall survival (Binabaj et al, 2018), emphasizing MGMT status as an independent indicator of a favorable prognosis. MGMT methylation could also be found in patient serum and strongly correlated with its presence in the tumor tissues (Fiano et al, 2014), suggesting that detection in blood samples could represent a re-DNA repair genes in astrocytoma 3 liable tool to predict response to TMZ treatment. MGMT methylation also disclosed its relevance as biomarker for other types of malignancies, including breast (Neto et al, 2012), colorectal (Lee et al, 2009), prostate (Cortese et al, 2012), cervical , gastric (Jin et al, 2014) and lung (Ostrow et al, 2010) cancers.…”
Section: Dna Repair Genes As Biomarkers Of Astrocytoma Aggressivenessmentioning
confidence: 99%
“…More recently, a meta-analysis of 10 eligible studies, including the MGMT methylation status of more than four thousand subjects, confirmed that patients bearing this genotype present longer overall survival (Binabaj et al, 2018), emphasizing MGMT status as an independent indicator of a favorable prognosis. MGMT methylation could also be found in patient serum and strongly correlated with its presence in the tumor tissues (Fiano et al, 2014), suggesting that detection in blood samples could represent a re-DNA repair genes in astrocytoma 3 liable tool to predict response to TMZ treatment. MGMT methylation also disclosed its relevance as biomarker for other types of malignancies, including breast (Neto et al, 2012), colorectal (Lee et al, 2009), prostate (Cortese et al, 2012), cervical , gastric (Jin et al, 2014) and lung (Ostrow et al, 2010) cancers.…”
Section: Dna Repair Genes As Biomarkers Of Astrocytoma Aggressivenessmentioning
confidence: 99%
“…12 CD79B mutations were detected in 83.1% of PCNS-DLBCLs by Nakamura et al 13 Hypermethylation of the CpG islands in the promoter regions is an important mechanism for the silencing of tumor suppressor genes and DNA repair genes. Previous studies have revealed that the gene which encodes the DNA repair enzyme O (6)-methylguanine-DNA methyltransferase (MGMT) was transcriptionally silenced by promoter methylation in several human tumors, including gliomas, 14,15 systemic lymphomas 16 and PCNS-DLBCL. 17 The MGMT protein can repair the damaging effect of alkylating chemotherapy agents on the tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Lavon et al . and further studies confirmed this possibility and also explored the correlations with outcome and longitudinal evolution during disease course . cfDNA methylation analysis has also been proposed for diagnostic purposes in gliomas using CDKN2A promoter methylation assessment .…”
Section: Circulating Cell‐free Nucleic Acids Analysismentioning
confidence: 82%